PENGARUH METODE BERNYANYI JARIMATIKA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MATERI PENJUMLAHAN KELAS 1 SEKOLAH DASAR - Nur Hidayah; Triman Juniarso; Amelia Widya Hanindita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the initial arithmetic skills of first grade students of SD Negeri 207 Gresik through the jarimatika singing method. The background of this study is the low quality of education in Indonesia, which is a challenge for education managers to improve the quality of learning. The method used in this study is a fun learning approach, where a lively classroom atmosphere can arouse children's enthusiasm for learning. Finger aids and the jarimatika singing method have proven effective in helping children master and remember arithmetic materials. This study involved two classes, namely the experimental class and the control class, with 29 students as research subjects in each class. The results of the study showed that the experimental class using the jarimatika singing method had an average posttest score of 80.52, while the control class only achieved an average of 68.62. based on the results of data analysis and discussion which can be concluded that there is an influence of the jarimatika singing method on the learning outcomes of first grade students of SD. Because Ho is rejected from the results of Equal Variances Assumed”, the Sig. (2-tailed) value is known to be 0.000 < 0,05, meaning Ho is rejected, thus it can be concluded that there is an influence on the research